2017
DOI: 10.1021/acs.est.6b04477
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Resolved Meta-Omics Ties Microbial Dynamics to Process Performance in Biotechnology for Thiocyanate Degradation

Abstract: 24Remediation of industrial wastewater is important for preventing environmental 25 contamination and enabling water reuse. Biological treatment for one industrial 26 contaminant, thiocyanate (SCN -), relies upon microbial hydrolysis, but this process is 27 sensitive to high loadings. To examine the activity and stability of a microbial community 28 over increasing SCN -loadings, we established and operated a continuous-flow bioreactor 29 fed increasing loadings of SCN -. A second reactor was fed ammonium sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 57 publications
6
59
0
Order By: Relevance
“…(Figure 3). As previously reported (Kantor et al 2017), the Rotifer was present in seven different samples (Rotifer_A-G, Figure 3), consistent with its persistence in the thiocyanate reactor community. All seven bins shared greater than 99% ANI (Supplemental Figure S4B) indicating they are likely the same species.…”
Section: Testing Eukrep In Recovery Of Eukaryote Genomes From Other Esupporting
confidence: 89%
See 2 more Smart Citations
“…(Figure 3). As previously reported (Kantor et al 2017), the Rotifer was present in seven different samples (Rotifer_A-G, Figure 3), consistent with its persistence in the thiocyanate reactor community. All seven bins shared greater than 99% ANI (Supplemental Figure S4B) indicating they are likely the same species.…”
Section: Testing Eukrep In Recovery Of Eukaryote Genomes From Other Esupporting
confidence: 89%
“…To test the broader application of EukRep, we applied the method to infant fecal samples and thiocyanate reactor samples in which eukaryotes had previously been identified , Raveh-Sadka et al 2015, Kantor et al 2015, Raveh-Sadka et al 2016, Kantor et al 2017.…”
Section: Testing Eukrep In Recovery Of Eukaryote Genomes From Other Ementioning
confidence: 99%
See 1 more Smart Citation
“…Case three, curation of a published incomplete genome to completion. Here we completed a published curated but incomplete genome belonging to the order Rickettsiales (Kantor et al 2017) . This genome was assembled de novo into a single circularizable 988 kbp scaffold, with two closely spaced gaps ( Figure S9a ).…”
Section: Case Studies Illustrating the Curation Of Draft Magsmentioning
confidence: 99%
“…Moreover, thiocyanate has been wildly employed in recovery of noble metals in metallurgy . It has been a widespread industrial contaminant found at especially high concentrations (up to 4000 mg/L) in gold mining effluents . Although the toxicity of thiocyanate is much smaller than that of cyanide , it can seriously influence the life of aquatic plants and animals and destroy the ecological environment when its concentration exceeds a certain degree.…”
Section: Introductionmentioning
confidence: 99%